2000
DOI: 10.1136/fn.83.1.f56
|View full text |Cite
|
Sign up to set email alerts
|

Body water content of extremely preterm infants at birth

Abstract: Background-Preterm birth is often associated with impaired growth. Small for gestational age status confers additional risk. Aim-To determine the body water content of appropriately grown (AGA) and small for gestational age (SGA) preterm infants in order to provide a baseline for longitudinal studies of growth after preterm birth. Methods-All infants born at the Hammersmith and Queen Charlotte's Hospitals between 25 and 30 weeks gestational age were eligible for entry into the study. Informed parental consent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…[7][8][9] This observation is consistent with the notion that in intrauterine growth restricted or SGA infants, the higher body water content is due to a lower lean body mass and fat content when expressed as percent birth weight. 10 Thus, it is somewhat counterintuitive to have a lower incidence of EPWL in SGA infants since the expectation is that a larger body fluid content 3,4 would result in more fluid loss after birth with greater accompanying weight loss.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…[7][8][9] This observation is consistent with the notion that in intrauterine growth restricted or SGA infants, the higher body water content is due to a lower lean body mass and fat content when expressed as percent birth weight. 10 Thus, it is somewhat counterintuitive to have a lower incidence of EPWL in SGA infants since the expectation is that a larger body fluid content 3,4 would result in more fluid loss after birth with greater accompanying weight loss.…”
supporting
confidence: 79%
“…Previous studies [7][8][9] have shown that small for gestational age (SGA) infants have a different body composition when compared with appropriate for gestational age (AGA) infants. Because SGA infants have less lean body mass and fat when expressed per kilogram body weight, their body water content is higher than their AGA counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the extra-cellular fluid compartment is a much higher percentage of total body weight [39][40][41]. It can also decrease over time as very preterm neonates can pass through a diuretic stage in the first few days of life [40,42], and this contraction of the extra-cellular fluid compartment may be a major contributor to weight loss in infants of this gestation and postnatal age [43].…”
Section: Parameter Valuesmentioning
confidence: 99%
“…Similarly, the distribution of water-soluble drugs may be increased in low birth weight infants because of their larger extracellular volume compared with term infants. 13 Low renal blood flow 14 and patent ductus arteriosus 15 during the first few days can markedly influence drug distribution through the body. Moreover, the low glomerular filtration rate in low birth weight infants 16 may lead to the accumulation of those drugs that are eliminated primarily by the kidneys, necessitating dose adjustment.…”
Section: Nddimentioning
confidence: 99%